2021
DOI: 10.3390/ijerph18179213
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating and Reflecting on Disability Prevalence Data Collected Using the Washington Group Tools: Results from Population-Based Surveys in Cameroon, Guatemala, India, Maldives, Nepal, Turkey and Vanuatu

Abstract: The Washington Group (WG) tools capture self-reported functional limitations, ranging from 6 domains in the Short Set (SS) to 11 in the Extended Set (ESF). Prevalence estimates can vary considerably on account of differences between modules and the different applications of them. We compare prevalence estimates by WG module, threshold, application and domain to explore these nuances and consider whether alternative combinations of questions may be valuable in reduced sets. We conducted secondary analyses of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…From an analysis of 2013 United States National Health Interview Survey data, the Group found a prevalence rate of 9.5% using all six questions and 9.3% using the first four [ 23 ]. Comparisons of using four or six questions in Vietnam found similarly low differences [ 24 ] and recent research, as noted, confirmed this [ 13 ]. We understand the argument that ensuring all six questions are asked may reduce the risk that anyone is missed.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…From an analysis of 2013 United States National Health Interview Survey data, the Group found a prevalence rate of 9.5% using all six questions and 9.3% using the first four [ 23 ]. Comparisons of using four or six questions in Vietnam found similarly low differences [ 24 ] and recent research, as noted, confirmed this [ 13 ]. We understand the argument that ensuring all six questions are asked may reduce the risk that anyone is missed.…”
Section: Discussionsupporting
confidence: 62%
“…Recent studies of use in government surveys and related programs have mostly focused on issues relating to disability prevalence. A study of use in population surveys identified prevalence figures from approximately 3% to 20% [ 13 ]. Contributing factors included the choice of question set and cut-off points.…”
Section: Introductionmentioning
confidence: 99%
“…The survey assessed disability based on four domains: seeing, concentrating (functioning impairment), moving around, and self-care (activity limitations/participation restriction), and the prevalence ranged from 2.3% in Ireland to 30% in South Africa. Using data from seven cross-sectional national surveys, and assessing disability across six functional domains, Mactaggart et al [ 15 ] estimated the prevalence of disability as ranging from 3.2% in Vanuatu to 14.1% in Turkey. At the same time, a study in Saudi Arabia found that the prevalence of disability was 3.3% using two of the six questions from the Washington Group (WG) on Disability Statistics [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disability was assessed based on the responses of the participants in two ways: Standard Threshold—those who reported ‘a lot of difficulty’ and ‘cannot do at all’ were considered as having a disability, while those reporting ‘no difficulty’ and ‘some difficulty’ were not regarded as having a disability, as recommended by the developers [ 12 ]. Wider Threshold- those reporting ‘some difficulty’, ‘a lot of difficulty’, and ‘cannot do at all’ were considered as having a disability [ 15 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation